P73 Systematic review of the use of physical activity devices as an adjunct to pulmonary rehabilitation in patients with chronic obstructive pulmonary disease. (15th November 2017) - Turner, BL; Kwok, M; Wilson, AM
Abstract : Introduction and Objectives: Approximately 1.2 million people in the UK are diagnosed with chronic obstructive pulmonary disease (COPD), which costs the NHS over £800 million per year in direct healthcare costs. Pulmonary rehabilitation (PR) is beneficial in improving health-related quality of life and exercise capacity. It is recommended in guidelines for COPD, however the initial beneficial effects diminish over time. This study reviewed the evidence for using any devices capable of detecting movement as an adjunct to PR, with the aim of prolonging improvements in physical activity (PA). Methods: The MEDLINE and CENTRAL databases were searched for the terms "pulmonary rehabilitation" AND ("COPD" OR "chronic obstructive pulmonary disease") AND ("pedometer" OR "biofeedback" OR "motion detector" OR "movement detector" OR "movement sensor" OR "motion sensor" OR "accelerometer" OR "smartphone"). Studies that met the following criteria were included: (1) adult population (age ≥18 years) undergoing pulmonary rehabilitation, (2) a primary clinical diagnosis of COPD, (3) the use of any device, as defined above, as an adjunct to pulmonary rehabilitation by comparison to a control group. Exclusion criteria were non-English studies and studies for which the full report was inaccessible via the researchers' OpenAthens and Shibboleth logins. Data was extracted and risk of bias assessed by two authors, using the Cochrane Risk of Bias tool. Results: Six studies fulfilled the inclusion criteria, with two showing statistically significant improvements in physical activity levels at the end of follow-up. The other four showed either no statistically significant benefit, or a benefit that was not sustained for the full follow-up period. The studies used a variety of devices, methodologies, and PR programmes. A summary of studies is provided in Table 1 . Conclusions: This review has found some evidence that the use of PA measurement devices may be beneficial in augmenting the PA gains achieved following PR, however it is not currently clear how to best calculate PA goals and how important face-to-face feedback is. Further research is therefore required to support the role of such interventions as a long-term intervention for management of COPD.